Simulações dos efeitos macroeconômicos do aumento dos investimentos públicos no Brasil - Bezerra, Arley Rodrigues (2013)
The objective of this work is to build a general equilibrium model, in order to perform counterfactual simulations of recent increases in public investment in Brazil to check effects on macroeconomic aggregates, as well as in social welfare. For the calibration of the model parameters and variables were used several databases, including IBGE, IPEADATA and Central Bank. The exercises consist of changing the values of the parameters for the composition ratio of public investment in the year 2010 in which the investments of public administration, which are supposed to complement private investment, had a participation of 53% of the share of public investment to GDP. The investments of the state enterprises, which, by definition, are substitutes for private investment, participated with 47% complementary. The simulation that directs 80% of public investment to public administration while the remaining 30% is invested by state enterprises provides long-term results in which the product would grow about 9.5% while the welfare would grow 8%, according with the proposed measure on the job. Furthermore, in simulations performed, even if the capital of the state enterprises have higher productivity than private capital, gains in welfare and growth would be obtained.